Pengaruh Komunikasi terhadap Efektivitas Kerja Karyawan pada PT. Maju Bersama Gunungsitoli - Jeliswan Berkat Iman Jaya Gea (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to describe the influence of communication on employee work effectiveness at PT. Maju Bersama Gunungsitoli. This study is motivated by suboptimal employee communication and the importance of effective communication to encourage effective and efficient employee work. This study uses a descriptive quantitative approach. The subjects of the study were 15 employees of PT. Maju Bersama Gunungsitoli who were selected using total sampling or saturated sampling techniques. Data collection techniques were carried out through library research and field research, namely observation and questionnaire distribution. Data analysis was carried out through classical assumption tests including validity and reliability tests, correlation coefficient tests, determination coefficient tests and hypothesis tests. The results of the study indicate that communication has a positive contribution or has a positive effect on employee work effectiveness. This is evidenced by the results of the hypothesis test which shows a calculated t value greater than the t table (3.207 > 2.160). In addition, the results of the determination coefficient test show that the influence of communication on employee work effectiveness is obtained by 41%. These results are understood that communication makes a significant contribution to employee work effectiveness. However, there are other potential factors influencing employee work effectiveness, amounting to 59%, that were not examined in this study. These factors could include work motivation, leadership, the work environment, work discipline, and other organizational factors.